Effect of sickle cell anemia awareness package on screening intention among grade 9 students of public schools in Tikapur municipality: a phase III intervention study. - Chaudhary,Santa Ram (2020)
ABSTRACT: Sickle cell anemia (SCA) is inherited red blood cell disorder. There are many sickle cell anemia conditions reported in Nepal till date, despite the fact that many people do not go to health facilities or screening camps for diagnosis. They do not have adequate knowledge about causes, diagnosis and treatment of sickle cell anemia. So, this study was conducted to find out the knowledge and attitude of students regarding sickle cell anemia as well as to evaluate the effect of SCA awareness package. This study was conducted in three phases and Health Belief Model was used as theoretical framework. Quantitative method was used in first phase while qualitative method was used in second phase. Third intervention phase was based on quasi-experimental study design. Sample size infirst phase was 481; third phase was 88 and 85 (intervention and control group respectively). After the 4 weeks of intervention, posttest was conducted. The duration of study was 6 months.Study revealed that nearly three fourth (72.6%) respondents have "median and below" knowledge on sickle cell anemia. Similar proportion (71.7%) respondents have "median and below" attitude regarding sickle cell anemia. However, on sickle cell anaemia screening knowledge four-fifth (78.6%) scored "median and below". Sex of respondents was significantly associated with knowledge on sickle cell anemia (p=0.025). Likewise, age and family type of respondents were significantly associated with the attitude on sickle cell anemia (p=0.039 and p= 0.018 respectively). Respondents sex and father's occupation were also significantly associated with sickle cell screening knowledge (p=0.001 and p=0.041 respectively). The change in knowledge, perception and screening intention among respondents in intervention group was more than control group. The actual change between intervention and control group was obtained as SCA knowledge (45.18%), perceived susceptibility (18.56%), perceived severity (10.73%), perceived benefits (5.1%) and perceived barrier (-31.88%) and screening intention (16.25%). Since the sickle cell awareness package was effective for increasing knowledge, perception and screening intention regarding sickle cell anemia among students.